Student's Creative Thinking Ability with The Lesson Study Design in Biology Content - Baiq Fatmawati; Nunung Ariandani; Maya Sasmita (Postgraduate, University of Mataram, 2021)
Some strategies were conducted by educators to create a conducive classroom atmosphere, and create collaborative learning so that students are accustomed to expressing their ideas, and opinions in learning, one of which is by implementing lesson study patterns for learning community. The research focus was to find out students' creative thinking skills in biological materials by using lesson study for learning community learning patterns. The respondents of the study were Grade X IPA students at SMA Negeri 1 Masbagik numbering 33 students. Data collection used a description test of biodiversity. The results of the description test were analyzed using the Scale Range Formula, the description test given referred to indicators of creative thinking ability i.e. fluency, flexibility, and originality and each answer was given a score of 3, 2 and 1. The results of the data analysis were that learning with lesson study patterns for learning community, students were able to produce creative ideas with a moderate category that is above 50%, while for the low and high categories the gain was below 50% in creative thinking indicators namely fluency, flexibility, and originality. To get used to students getting used to creative thinking, it took exercises in the creative thinking process either in the form of essay questions, or tasks that are implemented during the learning process